Behavioral Accounting / Human Information Processing in Accounting / The Coming Crisis in Accounting. - Birnberg, Jacob G.; Moriarty, Shane R. (The Accounting Review, 1990)
Reviews accounting books by Ahmed Belkaoui. `Behavioral Accounting'; `Human Information Processing in Accounting'; `The Coming Crisis in Accounting.'